Climate-induced migration in South Asia: Migration decisions and the gender dimensions of adverse climatic events - Bhatta, Gopal Datt; Aggarwal, Pramod K.; Poudel, S.; Belgrave DA (2015)
There is significant interest in determining the role of climate-induced shocks as a prominent driver on migration decisions of different groups of farmers in South Asia. Using data from a survey of 2,660 farm-families and focused group discussions in Bihar (India), Terai (plains) (Nepal) and coastal Bangladesh, we employed logistic regression to investigate household response towards migration and gender dimensions of adverse climatic events. The results suggest that migration decisions depend on farmers' unique resource profiles: (a) households that use migration to improve their resilience, mostly resource rich households; (b) households that have no alternative but to migrate, mostly poor farmers; and (c) households who cannot migrate due to different socio-economic obligations, mostly farmers with intermediate level of income that also includes women, children and elderly of different income profiles. These profiles represent a spectrum with households within a profile being closer to one or the other of the profiles on either side. They are not mutually exclusive and serve as a point of departure for further research to refine key explanatory variables. Given that some members of the household pursue migration as a result of adverse climatic events, government strategies are required to mitigate risks at destinations and create opportunities for the trapped populations.